Crystallization and preliminary X-ray analysis of SIII-SPIII, a ahospholipase A2 isolated from the venom of Bothrops jararacussu - De Azevedo Jr., Walter F. [UNESP]; Fontes, M. R M [UNESP]; Ward, Richard J.; Lombardi, F. R. [UNESP]; Cintra, A. C O; Giglio, José R.; Arni, Raghuvir K. [UNESP] (My University, 1998)
Large single crystals have been obtained of SIII-SPIII, a phospholipase A2 from the venom of Bothrops jararacussu. The crystals belong to the orthorhombic system space group C222, and diffract X-rays to a resolution of 1.9 Å. Preliminary analysis reveals the presence of one molecule in the crystallographic asymmetric unit. The crystal structure is currently being determined using molecular replacement techniques.